Refertilization of depleted mantle peridotite in the Nagaland–Manipur ophiolite, north‐east India: Constraints from PGE, mineral, and whole‐rock geochemistry. Issue 12 (15th March 2022) - Chaubey, Monika; Singh, Athokpam Krishnakanta; Singh, Birendra P.; Imtisunep, Sashimeren; Dutt, Amrita; Satyanarayanan, Manavalan; Premi, Kshetrimayum; Abhirami, Sethuraman G.
Abstract : This paper discusses whole‐rock geochemistry, mineral chemistry, and platinum group element (PGE) systematics of depleted mantle rocks (harzburgite and dunite) from the northern part of Nagaland–Manipur Ophiolite (NMO), north‐east India, to comprehend their source features, fractionation behaviour of PGE during magmatic evolution, and its tectonic origin. The studied ultramafic rocks are characterized by a low concentration of CaO (0.57–0.71 wt%), Al2 O3 (0.18–0.92 wt%) with ∑REE of 1.135–2.702 ppm and high concentrations of MgO (38.70–44.21 wt%), Cr (1, 843–4, 572 ppm), and Ni (894–4, 138 ppm). They show U‐shaped REE patterns [LREE and HREE enrichment (La/Sm)N  = 1.85–4.11, (Dy/Yb)N  = 0.51–0.85]. Olivine ranges Fo 88.18 to Fo92.23, whereas Cpx and Opx range En44.84 to En47.89 and En86.37 to En93.37 respectively. The chrome spinel Cr# [Cr/(Cr + Al)] and Mg# [Mg/(Mg + Fe 2+ )] are 0.47–0.83 and 0.31–0.60, respectively, which indicates recrystallization from a boninitic magma in a Supra‐Subduction Zone setting. Conventional thermometry indicates the equilibration temperatures of the dunite sample yielded high temperatures of ~850°C, suggesting their formation due to later interaction with high‐temperature percolating melts. The PGE contents in harzburgite are low (125.6–142.8 ppb) as compared to the dunite (248–360 ppb). They have high PPGE/IPGE and negative Pt* (Pt/Pt* = 0.73) anomaly, which is characteristic of re‐entry of PPGE into the system via reaction with percolating basaltic melt in the mantle wedge. Significantly higher concentration of PPGEs than IPGEs in the samples, indicating recrystallization of PPGEs with early sulphide fractionation. The presence of significant Rh and Pd enhancements relative to Pt in all samples suggests that Pt was removed during PGE fractionation. This could be one of the reasons for both harzburgite and dunite's sulphide undersaturation. PGE distribution in NMO ultramafic rocks was therefore validated as being governed by sulphide saturation in parental magma and altered not only by partial melting but also by fractionation during their production in the Supra‐Subduction Zone environment. Abstract : Depleted mantle rocks (harzburgite, dunite) of the Nagaland–Manipur Ophiolites, north‐east India, appear as fragmented masses connected with mafic rocks and oceanic pelagic sediments. Both rocks have U‐shaped REE patterns, indicating depletion in MREE in the mantle sequence, with platinum group element (PGE) levels in harzburgite being lower (125.6–142.8 ppb) than in dunite samples (248–360 ppb). S‐undersaturation signatures observed in harzburgite and dunite. As a result, we conclude that parental magma S‐saturation affects the distribution of PGEs in the NMO ultramafic rocks. The melting points of these harzburgites and dunites have been gradually rising (20%), which can be explained by generation due to interactions and recrystallization of the percolating melts. Our observations on whole‐rock, mineral chemistry, and PGE geochemistry suggest that the investigated depleted mantle harzburgite and dunites have been fertilized by reaction with percolating basaltic melt in the mantle wedge region of the subduction zone.